Telerehabilitacija - utopija ali svetla prihodnost? - Matjačić, Zlatko (Rehabilitacija (Ljubljana), 2009)
Telerehabilitation is a rapidly developing field of telemedicine that enables the provision of rehabilitation services in the user's home environment by means of communication technologies. The article starts with a short outline of the current state in telerehabilitation systems based on haptic robotics and virtual reality training tasks in rehabilitation of upper limbs. That is followed by a description of our own telerehabilitation system developed for balance training during standing. The article closes with a discussion on the open questions related to telerehabilitation that need to be addressed in the future development in order to fully integrate telerehabilitation into clinical practice.
Keywords: rehabilitacija; vocational rehabilitation; telerehabilitacija; ravnotežje; haptična robotika; navidezna resničnost